THEORETICAL FOUNDATIONS OF ORGANIZING MILITARY PEDAGOGICAL TRAINING FOR CADETS - Khaidarov Zhamol Gulommamatovich (American Journals, 2024)
This article expresses an opinion on modern views, problems and solutions for organizing the military-pedagogical process of cadets of higher military education.
Keywords: Emotion, emotional stability, mood, intelligence.